Game: On Instrumentalised Desire - Conradie, Pieter (The Stellenbosch Socratic Journal, 2022)
In this paper, I discuss two uses of the concept GAME in relation to the repression of desire. The first use refers to the common use of the term: board games, sports and riddles, while the second refers to sexual prowess. Following Herbert Marcuse’s concepts of surplus repression and the performance principle, I argue that the supposed liberation of desire in an advanced capitalist society transfigures desire into another consumable product under rational control. Such desire further alienates us from one another since relationships become a constant game of manipulation in which we seek to suppress, produce and negotiate desire. In a series of interludes, I then imagine societies with alternative expressions of desire. In doing so, I seek to describe as well as to perform a world free from excessive rationality. However, under academic strain, this project faces monumental inclinations to justify and explain what would otherwise be an honest form of playing. In the spirit of critical social theory, I sketch the reality of a game-driven society yet locate transformative potential in our radical intersubjectivity.